Neurofeedback course applying of high skilled gymnasts in competitive period - Strizhkova, O.; Cherapkina, L.; Strizhkova, T. (Journal of Human Sport & Exercise, 2012)
Carried out researches with 28 high skilled gymnasts (15 - main group, 13 - control group) allowed to define the neurofeedback influence on functional condition of the sportswomen in competitive period. Neurofeedback course promotes improvement of rapidity of complex coordinating movements` memorization, vestibular stability and self-estimation of functional condition. Also it conducts to alpha-rhythm power increasing at left hemisphere. Neurofeedback course efficiency is defined by index of change of course average alpha-rhythm power with 100% prognostic accuracy. Attention switching, attention stability and self-estimation of sleep and memory are predictors of neurofeedback course successfulness.